Teacher Training and Professional Development in Reading Instruction: A Comparative Study of GCC Countries - Allaith, Zainab A. (International Electronic Journal of Elementary Education, 2025)
This study examined the GCC reading teachers’ perceptions of the extent to which formal education and training addressed key areas of reading instruction, alongside their current professional development needs. Drawing on PIRLS teacher questionnaire data from Bahrain, Oman, Qatar, Saudi Arabia, and the UAE, descriptive and nonparametric analyses were conducted to answer the study’s questions. Results demonstrated that while pedagogy and assessment were generally well covered in teacher preparation programs, learning support, special education, and digital literacies were perceived as underemphasized. Across the region, most teachers reported moderate to high needs for professional development in areas such as comprehension strategies, language-related challenges, differentiation, integration of digital literacies, and assessment. Differences in perceived needs emerged across countries; however, teaching experience and prior training had negligible effect sizes on these needs. The findings highlight the importance of designing pre-service and in-service programs that are responsive to context-specific student needs and classroom realities, with sustained, targeted support throughout teachers’ careers to enhance literacy instruction outcomes. These implications hold strong potential to improve instructional effectiveness and advance student literacy outcomes.